Explanatory Factor analysis to determining the risk factors of cardiovascular disease: A hospital-based case-control study - mohammed, ebtehag mustafa (Jour Med Resh and Health Sci, 2020)
Introduction: Cardiovascular disease is one of the most preventable causes of death in the world since the majority of its risk factors are preventable or controllable. The aim: this study was conducted to determine risk factors for cardiovascular disease among patients admitted to wad Medani heart Centre, wad Medani, Sudan. Materials and methods: A hospital-based case-control study was conducted and carried out in Gezira state (wad Medani heart Centre), Data collection lasted for almost one year (From 2018 to 2019), via structured face-to-face interviews of 800 respondents in wad Medani heart hospital. cross tabs and chi-squared tests were utilized to analyze the association between the dependent and independent variables, factor analysis is used to profile the most effective socioeconomic factors of cardiovascular disease, all the significant values were set up at p<0.05, several risk factors for cardiovascular disease were measured on 750 patients with and 50 patients without this disease. Next, factor analysis was performed to identify underlying variables, or factors, that explain the pattern of correlations within a set of observed risk factors. To obtain more accurate results, the factor analysis was performed for each of the survey axes separately. The limiting Eigenvalue is taken as 0.1 Results: the result of factor analysis revealed several variables as risk factors for cardiovascular disease, the most important of them is locality, age, Renal disease, smoking, passive smoking, drinking alcoholic, operated heart injury and using oil cooking. Conclusion: older individuals who practice habitual and behavioural such as smoking, drinking alcoholic, eating oil cooking and not dealing with chronic disease as well are more likely to develop cardiovascular disease. Keywords: risk factors, cardiovascular disease, chi-squared tests, factor analysis